Normalisation with Israel who seeks to gain ? - Abdul Hadi Awang (Pustaka Permata Ummah Sdn Bhd, 2020)
This book seeks to enlighten and raise awareness among the readers, especially in Malaysia, about the efforts to normalise the ties with Israel by several Arab countries. In addition, this provides an overview of the implications of this normalisation effort on the survival of Palestine and our standpoint in responding to the political turmoil in the Middle East.